2023
DOI: 10.1021/acsbiomedchemau.3c00059
|View full text |Cite
|
Sign up to set email alerts
|

Proteases Involved in Leader Peptide Removal during RiPP Biosynthesis

Sara M. Eslami,
Wilfred A. van der Donk

Abstract: Ribosomally synthesized and post-translationally modified peptides (RiPPs) have received much attention in recent years because of their promising bioactivities and the portability of their biosynthetic pathways. Heterologous expression studies of RiPP biosynthetic enzymes identified by genome mining often leave a leader peptide on the final product to prevent toxicity to the host and to allow the attachment of a genetically encoded affinity purification tag. Removal of the leader peptide to produce the mature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 202 publications
0
5
0
Order By: Relevance
“…This analysis identified several clusters of glycocin glycosyltransferases (Figure ). Glycosyltransferases such as SvGT, EnfC, and GccA, although functioning similarly, were not classified within the SunS/ThuS subfamily (InterPro: IPR026499). Glycocin glycosyltransferases were thus further identified by their genomic proximity to C39 peptidases (InterPro: IPR005074), which cleave leader peptides from precursor glycocins . An SSN analysis also revealed clusters of glycosyltransferases within flagellar biosynthetic gene clusters containing flagellin genes (InterPro: IPR001492). , Sequence alignments and structure predictions using AlphaFold2 , suggest that these glycosyltransferases possess extended C-terminal α-helical domains with variable lengths (Figures , S1, and S2).…”
Section: Resultsmentioning
confidence: 99%
“…This analysis identified several clusters of glycocin glycosyltransferases (Figure ). Glycosyltransferases such as SvGT, EnfC, and GccA, although functioning similarly, were not classified within the SunS/ThuS subfamily (InterPro: IPR026499). Glycocin glycosyltransferases were thus further identified by their genomic proximity to C39 peptidases (InterPro: IPR005074), which cleave leader peptides from precursor glycocins . An SSN analysis also revealed clusters of glycosyltransferases within flagellar biosynthetic gene clusters containing flagellin genes (InterPro: IPR001492). , Sequence alignments and structure predictions using AlphaFold2 , suggest that these glycosyltransferases possess extended C-terminal α-helical domains with variable lengths (Figures , S1, and S2).…”
Section: Resultsmentioning
confidence: 99%
“…At present, it is unclear whether modified ApyA will be further processed by a leader peptidase. The BGC does not encode a protease, but akin to other RiPPs, the protease could be encoded elsewhere on the genome . Attempts to elicit the production of the final product by B. thailandensis E264 to provide information on proteolytic processing were unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…The leader peptide is recognized by modification enzymes that are usually encoded in the same biosynthetic gene cluster (BGC) to receive post-translational modifications on the core peptide. Subsequently, the leader peptide is removed by protease cleavage to yield the mature peptide with desired bioactivity. , Bioinformatic studies have found great potential for RiPP discovery from the microbiome . Recent advances in metagenomic sequencing and assembly have made vast amounts of environmental microbial genomes available for investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the leader peptide is removed by protease cleavage to yield the mature peptide with desired bioactivity. 7 , 8 Bioinformatic studies have found great potential for RiPP discovery from the microbiome. 9 Recent advances in metagenomic sequencing and assembly have made vast amounts of environmental microbial genomes available for investigation.…”
Section: Introductionmentioning
confidence: 99%